Hey! Hear me out. Voices of Deaf and Hard of Hearing Mob on the National Disability Insurance Scheme in the Northern Territory - Barney, Jody; Alexandra Devine; Howard, Damien; Yi Yang; NICHOLAS DISNEY; Peter Summers; Ashley McAllister (2023)
This report outlines key factors participants highlighted as influencing their experiences within the NDIS, in particular the utilisation of their NDIS plans. We propose potential policy and practice considerations that – when led, co-designed and progressively delivered by First Nations communities - may help improve opportunities for First Nations people who are Deaf or Hard of Hearing to engage with and benefit from the NDIS.